HUBUNGAN PENGETAHUAN DENGAN SIKAP ORANG TUA TERHADAP PENINGKATAN STIMULASI PERKEMBANGAN ANAK USIA 4-5 TAHUN - Erlina Hayati; GF Gustina Siregar (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
This article presents the results of research on the Relationship of Knowledge with Attitudes of Parents to Increased Stimulation of Development of Children 4-5 Years Old in XVIII Hamlet, PayaBakung Village, Hamparan Perak Subdistrict, Deli Serdang District in 2018 which aims to determine parents' knowledge of parental interest in stimulating . This research is an analytic survey that tries to explore how and why health phenomena occur. The population in this study were parents who had children aged 4-5 years as many as 30 people in VXII Hamlet, PayaBakung Village, Hamparan Perak District, Deli Serdang Regency. While the sampling technique in this study using total sampling technique is the number of population sampled as many as 30 people. From the results show that almost all parents who have children aged 4-5 years know how to stimulate good development for their children if children cannot experience delays that can be caused by lack of fulfillment in children, in which is the need to play. Childhood should be a period of play that is expected to foster maturity in growth and development, so that if the period is not used as well as possible, of course, it will eventually disrupt the growth of children.